Influence of Storage of Probiotic Broth Culture Filtrates on Their Antimicrobial Activity - Isaienko, Olena Yu.; Knysh, Oksana V.; Babych, Yevgen M.; Kompaniets, Antonyna M.; Osetsky, Oleksandr I.; Polianska, Valentyna P.; Zachepylo, Svitlana V. (Problems of Cryobiology and Cryomedicine, 2017)
Nowadays there is no standard efficient technology for long-term storage of metabolite-containing products of microbial origin as well as no data about the advantages and expediency of using one or another method of storage for these products. Determining the optimal storage conditions will prevent the loss of biological activity of metabolites during storage both for scientific research and production. Metabolites were obtained by isolation from the producers by means of centrifugation and filtration after culturing probiotics in a liquid nutrient medium. We studied antimicrobial activity of filtrates of probiotic culture liquids with various inoculation doses right after obtaining and storage for 60 days in liquid, frozen and frozen-dried state at (4 ± 1)°C, (–23 ± 1)°C and under hypothermic conditions (4 ±1)°C, respectively. The storage of probiotic broth culture filtrates under the mentioned above conditions did not result in a significant reduction of their antimicrobial activity. The obtained results can be used when developing commerciol synbiotics. Probl Cryobiol Cryomed 2017; 27(4): 311–321